PREVALENSI Eimeria spp. PADA TERNAK KELINCI - Arina Umi Faizah; Diana Indrasanti; Muhamad Samsi (Jambura Journal of Animal Science, 2022)
This study was aimed to determine the prevalence of Eimeria spp., to determine the differences in the prevalence of Eimeria spp. in rabbits of various ages and to know the species of Eimeria spp. which infect rabbits of various ages in Cilongok District, Banyumas Regency. The main objects of observation were weaning rabbits (1-5 weeks), weaning (6-24 weeks) and adults (24 weeks). The research method used is survey method with purposive sampling technique. The data were analyzed using the method of description and chi square. The sample used was rabbit feces as much as 5 grams per head with a sample of 96 rabbits in three age periods each totaling 32 rabbits. The results of the analysis showed that the prevalence of Eimeria spp. in rabbits the weaning period was 96.88%, after weaning was 96.88% and adults were 78.13%, and the prevalence of Eimeria spp. overall by 90.62%. The species Eimeria spp. that infect rabbits are Eimeria exigua, Eimeria perforans, Eimeria piriformis, Eimeria flavescens, Eimeria stiedai, Eimeria intestinalis, Eimeria media, Eimeria coecicola and Eimeria magna. P0.05 indicates that there is a difference in the prevalence of Eimeria spp. in rabbits of various ages in Cilongok District, Banyumas Regency. Prevalence of Eimeria spp. very significant effect on weaning, weaning and adult rabbits.